Spontaneous Spinal Epidural Hematoma Complicated by Pulmonary Embolism During Pregnancy: A Case Report - Jiang, Wei; Tan, Xuan-Yu; Li, Jia-Ai; Dong, Ming (Frontiers in Medicine, 2022)
Background Spontaneous spinal epidural hematoma, without discernable underlying conditions, is considered a neurological emergency, and is rare during pregnancy. Case Presentation We report the case of a 24-year-old patient at 37 weeks of gestation. She had back pain that progressed to paraplegia of both lower limbs within 2 days. Thoracic magnetic resonance imaging revealed a lesion behind the spinal cord at the T5–T6 level, suggestive of spontaneous spinal epidural hematoma. Due to the rapid recovery of muscle strength in her lower limbs after an emergency cesarean section, we used methylprednisolone therapy to reduce spinal edema rather than decompression of the spinal canal. We incidentally found that the patient’s left pulmonary artery was occluded. In consideration of spontaneous spinal epidural hematoma as relative contraindication to anticoagulation, and in the absence of pulmonary embolism symptoms, including good partial oxygen pressure, we did not administer anticoagulant therapy. The patient’s condition improved rapidly in the following week. Conclusion Spontaneous spinal epidural hematoma concomitant with pulmonary artery embolism is an extremely rare manifestation during pregnancy. As exemplified by our case, desirable treatment outcomes are possible under such cases.